A new stiletto fly in the genus Anabarhynchus Macquart (Diptera: Therevidae)from Fiji - Irwin, Michael E.; Winterton, Shaun L. (Zootaxa, 2019)
An unusual species of Anabarhynchus Macquart is described and represents the first record of a stiletto fly from Fiji.